Co-benefit of climate mitigation on air quality and human health in Asian countries - Yang Xie; Hancheng Dai*; Xu, Xinghan; Fujimori, Shinichiro; Hasegawa, Tomoko; Masui, Toshihiko; Kurata, Gakuji (Environment International, 2018)
Climate change mitigation involves reducing fossil fuel consumption and greenhouse gas emissions, which is expensive, particularly under stringent mitigation targets. The co-benefits of reducing air pollutants and improving human health are often ignored, but can play significant roles in decision-making. In this study, we quantified the co-benefits of climate change mitigation on ambient air quality and human health in both physical and monetary terms with a particular focus on Asia, where air quality will likely be degraded in the next few decades if mitigation measures are not undertaken. We used an integrated assessment framework that incorporated economic, air chemistry transport, and health assessment models. Air pollution reduction through climate change mitigation under the 2 °C goal could reduce premature deaths in Asia by 0.79 million (95% confidence interval: 0.75–1.8 million) by 2050. This co-benefit is equivalent to a life value savings of approximately 2.8 trillion United States dollars (USD) (6% of the gross domestic product [GDP]), which is decidedly more than the climate mitigation cost (840 billion USD, 2% of GDP). At the national level, India has the highest potential net benefit of 1.4 trillion USD, followed by China (330 billion USD) and Japan (68 billion USD). Furthermore, in most Asian countries, per capita GDP gain and life value savings would increase with per capita GDP increasing. We robustly confirmed this qualitative conclusion under several socioeconomic and exposure-response function assumptions.